Assessment of sperm quality and short term preservation of sperm in grey mullet Mugil cephalus Linnaeus, 1758 - Ramachandran, Balamurugan; Natesan, Munuswamy (Indian Journal of Fisheries, 2016)
Quality of fresh milt of grey mullet Mugil cephalus Linnaeus, 1758 was assessed based on motility grade, motility duration, sperm count and seminal plasma osmolality. Freshly collected milt from live males (n=17) were examined individually for motility assessment. Motility grade was four in fifteen samples whereas three in other two samples analysed. Other sperm quality parameters such as motility duration, sperm density and seminal plasma osmolality were : 421.38±137 sec, 1.67±0.3x108 nos. ml-1 and 362.28±79.13 m Osmol kg-1 respectively. To standardise short term preservation of sperm, four different extenders such as ringer solution for marine fish, modified marine fish ringer solution, V2E extender and honey in fish ringer solution were experimented. The results indicated that short term preservation at 4oC over a period of 10 days with V2E extender at 1:1 ratio significantly (p<0.05) retained the highest sperm motility grade (2.6±0.5) over other dilutions such as 1:2 and 1:3 on 5th day. However, on 10th day of observation, sperms were immotile after activation with seawater, in undiluted as well as diluted milt samples. This probably indicates that V2E extender is effective for short term preservation of sperm in grey mullet.